Atrophic Myenteric and Submucosal Neurons Are Observed in Parkinson’s Disease - Bodil Ohlsson; Elisabet Englund (Parkinson's Disease)
Aim. Parkinson’s disease is often accompanied by gastrointestinal symptoms, especially constipation. Microscopic studies of the enteric nervous system and enteric neuropathy have often been performed by immunostaining in the myenteric plexa. The aim of the present study was to examine whether pathologic changes could be identified by conventional hematoxylin and eosin (H&E) staining and could also be seen in the submucosal plexa. Materials and Methods. In 20 deceased cases (11 male/9 female) of Parkinson’s disease, the intestinal tract was investigated for potential neuroganglionic disease. Ten cases (7 male/3 female) of non-Parkinson, intestinally asymptomatic individuals were used as controls. Specimens from the jejunum and colon were sampled. The material was treated with standard histopathological procedures, i.e., fixed in formaldehyde solution, dehydrated and embedded in paraffin, sectioned at 5 μm thickness, and stained with H&E and immunostaining for α-synuclein. Results. In 15 cases (7 male/8 female) of Parkinson’s disease, atrophic/pycnotic nerve plexus cells were present, i.e., signs of ganglionic degeneration in the submucosal and/or myenteric plexa, mostly identified in both loci, by H&E staining. In some cases, the degenerative signs were mild, however, corroborated by findings of α-synuclein deposits in the ganglion cells. The remaining 5 cases showed no signs of degeneration in the H&E staining, but immunostaining revealed minimal α-synuclein deposits in 3 cases. None of the controls showed any ganglionic degeneration/α-synuclein deposits. Conclusion. It seems possible to identify a morphologic intestinal disease substrate in Parkinson’s disease by H&E staining, showing ganglion cell pycnosis and degeneration in both plexa. This finding may indicate a potential to diagnose enteric neuropathy in highly accessible sites.